2022
DOI: 10.1101/2022.02.23.481555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional and cell type-specific afferent and efferent projections of the mouse claustrum

Abstract: The claustrum (CLA) is a conspicuous subcortical structure interconnected with cortical and subcortical regions. However, its regional anatomy and cell-type-specific connections in the mouse remain largely undetermined. Here, we accurately delineated the boundary of the mouse CLA and quantitatively investigated its inputs and outputs brain-wide using anterograde and retrograde viral tracing and fully reconstructed single claustral principal neurons. At a population level, the CLA reciprocally connects with all… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 100 publications
4
15
2
Order By: Relevance
“…This could indicate that Esr2+ CLA neurons are more likely to innervate RSP than PFC. This would be consistent with the finding that neurons in what some refer to as the CLA "core", which is likely to correspond with the location of these Esr2+ neurons, project strongly to RSP (Marriott et al, 2020;Wang et al 2022).…”
Section: Replication Of Results In Esr2-ai32 Transgenic Linesupporting
confidence: 86%
See 4 more Smart Citations
“…This could indicate that Esr2+ CLA neurons are more likely to innervate RSP than PFC. This would be consistent with the finding that neurons in what some refer to as the CLA "core", which is likely to correspond with the location of these Esr2+ neurons, project strongly to RSP (Marriott et al, 2020;Wang et al 2022).…”
Section: Replication Of Results In Esr2-ai32 Transgenic Linesupporting
confidence: 86%
“…It is quite likely that these different molecular targeting methods resulted in different populations of CLA or non-CLA neurons expressing ChR2, which when stimulated could produce different effects in the cortex. For example, while Jackson et al (2018) found that claustrum neurons innervated layer 6 of PFC more strongly than layer 2/3, other studies have found the opposite pattern (Fodoulian et al, 2020;Wang et al, 2017;Wang et al 2022), which may explain differences between their findings of a primarily inhibitory effect, and ours and those of Fodoulian et al (2020) of a primarily excitatory effect.…”
Section: Differences With Previous Studiescontrasting
confidence: 63%
See 3 more Smart Citations